2017
DOI: 10.1016/j.jaci.2016.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Human regulatory B cells control the T FH cell response

Abstract: Human Breg cells control T cell maturation, expand follicular regulatory T cells, and inhibit the T cell-mediated antibody secretion. These novel observations demonstrate a role for the Breg cell in germinal center reactions and suggest that deficient activities might impair the T cell-dependent control of humoral immunity and might lead to the development of aberrant autoimmune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 51 publications
1
73
0
Order By: Relevance
“…Consistently, Achour et al. have further demonstrated that human Breg cells control Tfh cells maturation, expand Tfr cells, and inhibit Tfh cell–mediated antibody secretion . These observations highlight the pleiotropic functions of both Tfr and Tfh cells in the modulation of anti‐ and proatherosclerotic immune processes in an Apoe −/− mouse model.…”
Section: T and B Cells And Their Mutual Regulation In Atherosclerosissupporting
confidence: 53%
See 1 more Smart Citation
“…Consistently, Achour et al. have further demonstrated that human Breg cells control Tfh cells maturation, expand Tfr cells, and inhibit Tfh cell–mediated antibody secretion . These observations highlight the pleiotropic functions of both Tfr and Tfh cells in the modulation of anti‐ and proatherosclerotic immune processes in an Apoe −/− mouse model.…”
Section: T and B Cells And Their Mutual Regulation In Atherosclerosissupporting
confidence: 53%
“…Its atheroprotective function is derived by its capacity to inhibit Tfh cells via TGF‐β secretion, its direct up‐regulation of lymphangiogenesis, and also by the creation of a positive loop between Tfr and Breg cells, itself a Tfr cell activator . In presence of Breg cells, the differentiation of CD4 + cells in Tfh cells during atherosclerosis is diminished and, in turn, Tfh cell population blocks Breg cells by secreting IL‐4 . IL‐4 cytokine is also important on the down‐regulation of lymphangiogenesis…”
Section: T and B Cells And Their Mutual Regulation In Atherosclerosismentioning
confidence: 99%
“…It has been recognized that Tregs plays an indispensable role in ICI resistance at the present stage [34]. Similarly to Tregs, a subset of B cells are identified as immune inhibitory cells which are termed Bregs [35]. Bregs could inhibit inflammation response by increasing the generation of PD-L1 and cytokines such as IL-10 [36,37].…”
Section: Regulatory Immune Cellsmentioning
confidence: 99%
“…Signals for Bregs activation include TLR and CD40 stimulation, BCR signaling, and CD80/CD86 expression. 31 These 43 (2) Bregs induce the conversion of naïve CD4 + T cells into FoxP3 + Tregs, which is mediated by TGF-secretion and cell-to-cell contact between T and B cells. 44 Bregs also directly induce the differentiation of Tregs, which may contribute to the global suppression of inflammatory responses.…”
Section: Regulatory B Cellsmentioning
confidence: 99%